Impact of Adrenal Hormone Supplementation on Bone Geometry in Growing Teens With Anorexia Nervosa - DiVasta, Amy D.; Feldman, Henry A.; O'Donnell, Jennifer M.; Long, Jin; Leonard, Mary B.; Gordon, Catherine M. (Journal of adolescent health, 2019)
Adolescents with anorexia nervosa (AN) have decreased dehydroepiandrosterone (DHEA) and estrogen concentrations that may contribute to skeletal deficits. We sought to determine whether DHEA + estrogen replacement (ERT) prevented bone loss in young adolescents with AN. We recruited females with AN (n = 70, ages 11–18 years) into a 12-month, randomized, double-blind placebo-controlled trial. Participants were randomized to oral micronized DHEA 50 mg + 20 mcg ethinyl estradiol/.1 mg levonorgestrel daily (n = 35) or placebo (n = 35). Outcomes included serial measures of bone mineral density (BMD) by dual-energy X-ray absorptiometry (total body, hip, spine) and peripheral quantitative computed tomography (pQCT; tibia). Magnetic resonance imaging of T1-weighted images of the left knee determined physeal status (open/closed). Sixty-two subjects completed the trial. Physeal closure status was the strongest predictor of aBMD changes. Among girls with open physes, those who received DHEA + ERT showed a decline in BMD Z-scores compared with those receiving placebo, whereas there was no effect in those with at least one closed physis. Treatment did not affect any pQCT measures, regardless of physeal closure status. Combined DHEA + ERT did not significantly improve dual-energy X-ray absorptiometry or pQCT BMD measurements in young adolescent girls with AN, in contrast to an earlier trial showing benefit in older adolescents and young women. In girls with open physes, the mean change in the placebo arm was greater than that of the DHEA + ERT group. We conclude that DHEA + ERT is ineffective for preserving bone health in growing young adolescents with AN at the dose and route of administration described in this report.